RETRACTED: Optimization of pneumatic vortex processing for enhanced durability and reliability of machine parts - Fayzimatov Shukhrat; Mardonov Bakhtiyor; Khusanov Bakhtiyor; Fayzimatov Jasur; Sadirov Shokhrukh; Khusanov Yunusali (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001